MAKNA TEOLOGI DALAM NOVEL TUHAN MAHA ASYIK SUDJIWO TEDJO DAN DR. MN. KAMBA - Rahmat Firdaus (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2018)
AbstractGod, with its various mysteries, has given man the element that the search for Him for a search which - apart from being a continuous and unending activity - also gives pleasure. That is why God is most fun: either as an object of study, or as the goal of the entire axis of human activity. The author's understanding of God is very interesting to know, because this book of God is Most Fun is very different from other Theology books. The thinking method used is hermeneutics. The results of research on the novel Tuhan Maha Asik written by Sudjiwo Tedjo and DR. M N. Kamba, shows a direction in unique stories, starting from the discussion of wayang, marhain, worms, self and so on, which is presented with analogies in the style of children. The theological meaning contained in this book is theology of authentic self. Where we can know God through each human being, the self that is meant here is a natural self, not a self that has been entered by concepts formed from society or from outside.